2021
DOI: 10.1109/access.2021.3105750
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal D2D Small Cell Allocation and On-Demand Deployment for Microgrids

Abstract: Microgrids in smart grid development create a new era towards resilient energy supply. In turn, They also render complicated cyber-physical system development towards high scalability and comprehensiveness. Heterogeneous Small Cell based Networks (HSCNs) endow a suitable cyber infrastructure for microgrid based cyber-physical systems. To tackle this emerging research area, this paper proposes a Spatiotemporal Device-to-device communication based HSCN Deployment scheme for Microgrid based Smart grid Development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…PSO algorithm has a great potential to optimize parameter settings (Behera et al, 2016). Apart from industrial processes the applications relating to power system can be found in the literature this research is focused on the power system application and optimization (Ehsan et al, 2021;Shehzad et al, 2021;Chi et al, 2021;Autonomous, 2021;Guasti Junior and Santos, 2021;Lau and Lim, 2018;Fan et al, 2019;Hu and Eberhart, 2002;Dashtdar et al, 2022;Soliman et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…PSO algorithm has a great potential to optimize parameter settings (Behera et al, 2016). Apart from industrial processes the applications relating to power system can be found in the literature this research is focused on the power system application and optimization (Ehsan et al, 2021;Shehzad et al, 2021;Chi et al, 2021;Autonomous, 2021;Guasti Junior and Santos, 2021;Lau and Lim, 2018;Fan et al, 2019;Hu and Eberhart, 2002;Dashtdar et al, 2022;Soliman et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Going forward, the format used to indicate the weights and biases associated with a neuron is as follows W layer number (neuron number) Input number b layer number Bias number for that input Here, we have two inputs and four neurons in each hidden layer. So, the corresponding weighted matrixes can be written as (Chi et al, 2021),…”
Section: Mathematical Modelingmentioning
confidence: 99%